2015
DOI: 10.3389/fnins.2015.00220
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic dysfunction in Alzheimer's disease

Abstract: The brain noradrenergic system supplies the neurotransmitter norepinephrine throughout the brain via widespread efferent projections, and plays a pivotal role in modulating cognitive activities in the cortex. Profound noradrenergic degeneration in Alzheimer's disease (AD) patients has been observed for decades, with recent research suggesting that the locus coeruleus (where noradrenergic neurons are mainly located) is a predominant site where AD-related pathology begins. Mounting evidence indicates that the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 150 publications
(179 reference statements)
6
123
0
Order By: Relevance
“…Furthermore, it was also proposed that, if NAergic REM-OFF neurons do not cease activity, the NA level would rise in the brain and that elevated NA levels would be responsible for REMS loss-associated effects and symptoms. Indeed, our contention was supported by indirect, independent, and isolated experimental studies as well as by clinical observations (Mallick and Singh, 2011; Gannon et al, 2015); however, direct evidence particularly from in vivo studies was lacking. Therefore, in this study using tyrosine hydroxylase (TH)-siRNA and TH-shRNA in a separate group of normal rats, we downregulated TH in the LC neurons inhibiting NA synthesis in REM-OFF neurons.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, it was also proposed that, if NAergic REM-OFF neurons do not cease activity, the NA level would rise in the brain and that elevated NA levels would be responsible for REMS loss-associated effects and symptoms. Indeed, our contention was supported by indirect, independent, and isolated experimental studies as well as by clinical observations (Mallick and Singh, 2011; Gannon et al, 2015); however, direct evidence particularly from in vivo studies was lacking. Therefore, in this study using tyrosine hydroxylase (TH)-siRNA and TH-shRNA in a separate group of normal rats, we downregulated TH in the LC neurons inhibiting NA synthesis in REM-OFF neurons.…”
Section: Introductionmentioning
confidence: 75%
“…While much of the research focuses on the cholinergic and glutamatergic pathways, recently scientists have proposed changes in a host of other neurotransmitters (174,175).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…In vitro, NE increases IkB α [107], an inhibitor of proinflammatory transcription factor NF-kB. Inflammation is an important component in AD pathogenesis and promotes microglial activation [108], complement cascade, and inflammatory cytokine release [109] with nitric oxide activation. Animal studies have shown anti-inflammatory effects of pretreatment with a β -adrenergic receptor agonist [109] and α 2 receptor antagonist [110] on inflammation development in neurons after injection of β amyloid into LC-ablated animals.…”
Section: Role Of Lc/ne System In Neuropathologiesmentioning
confidence: 99%
“…Inflammation is an important component in AD pathogenesis and promotes microglial activation [108], complement cascade, and inflammatory cytokine release [109] with nitric oxide activation. Animal studies have shown anti-inflammatory effects of pretreatment with a β -adrenergic receptor agonist [109] and α 2 receptor antagonist [110] on inflammation development in neurons after injection of β amyloid into LC-ablated animals. It is important to note that some discrepancies exist between preclinical animal studies and clinical human studies: LC in animal AD models tends to be involved in late stages of pathology, compared to its degeneration in early disease progression in humans.…”
Section: Role Of Lc/ne System In Neuropathologiesmentioning
confidence: 99%